Isolated carcinomatosis of the abdominal cavity in women: the features of immunophenotypes and morphometric parameters. - О. V. Poslavska; I. S. Shponka; O. A. Savchenko; M. Yu. Petrova (Medičnì Perspektivi, 2018)
Patients with isolated abdominal carcinomatosis are traditionally treated similarly to patients with ovarian cancer stage III/IV. Despite histological, molecular and clinical similarities, this approach leaves no room for studying the individual biology of this phenotype of cancer of unknown primary localization. In addition, some metastases of gastrointestinal, pancreatic-biliary or endometrial adenocarcinomas simulate the histological and/or immunohistochemical (IHC) characteristics of primary ovarian adenocarcinomas. Over the past three decades, understanding the biology and pathways of intra-abdominal dissemination of tumors, taking into account the protective function of the peritoneal barrier against further tumor spreading, has led many researchers to consider the concept of peritoneal carcinomatosis as a locoregional disease. In the absence of other systemic metastases, new multimodal approaches combining aggressive cytoreductive surgery, intraperitoneal hyperthermia chemotherapy, and systemic chemotherapy are considered promising for improving disease control and increasing survival. Materials and methods. A retrospective analysis of clinical data, histological and IHC characteristics of biopsy material of 24 women with isolated abdominal carcinomatosis at the age of 28 to 81 years (mean 56.29±14.68, median 58.5) and 46 cases of primary ovarian tumors of women at the age of 27 to 76 years (mean 52.17±12.72, median 53.5), was performed to determine differential diagnostic criteria. IHC profile of primary ovarian tumors determined the most specific markers of cytokeratin C7 and CA125 (mucin 16), which in 43 out of 46 (93.48%) and 37 of 46 (80.43%) were respectively positive at least partially. It should be noted that 1 undifferentiated carcinoma was negative for both markers, only for SC7-2 mucinous adenocarcinomas and 1 low-grade, but only for CA125-2 endometrioid, 2 light-celled, 1 undifferentiated carcinoma and 4 low-grade adenocarcinomas (the latter were regarded as primary in exclusion of other localizations on the basis of a complete survey). Receptors to estrogens were determined in 14 of 46 (30.43%) of observations, which indicates their prognostic, and not diagnostic significance. In the group of women with isolated carcinomatosis of the abdominal cavity, SK7 was identified in 21 of 24 (87.5%) observations, CA125 in 16 of 24 (66.67%), all of whom had SC7 immunoreactivity, but only 9 of them demonstrated the presence of estrogen receptors, and 6 – serous phenotype (WT-1+), and 1 – mesothelioma (CK7 +, calretinin +). It should be noted that CA125-partially positive tumor patterns were often mixed with undifferentiated and nopapillary tumor deposits. These women were older than of the entire subgroup (mean 61.4 ± 10.08, median 61), but without significant difference (p>0.05). Conclusions. Only 2/3 of the investigated cases of carcinomatosis without primary localization in women after IHC research can be convincingly attributed to ovarian metastases for the application of appropriate therapy. Other 33.33% percent in our study were divided into 1 - neuroendocrine cancer (Chromogranin +, Synaptophysin +), 3 - colorectal (CK20 + CDX2 +), 2 - moderately and 1 - low-grade carcinomas with doubtful immunophenotypes (CK20+/-CDX2-/+CK7-/+Vimentin -/+), as well as 1 mesothelioma.